2019
DOI: 10.1111/ppa.13003
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic diversity across pathogen populations responsible for the global emergence of boxwood blight identified using SSRs

Abstract: Boxwood blight is an emerging disease of ornamental as well as native boxwood. The disease became widely established in Europe at the beginning of the 21st century, prior to its more recent discovery in North America and Asia. Two sister‐species of fungi cause the disease, Calonectria pseudonaviculata (Cps) and C. henricotiae (Che). Prior efforts to quantify intraspecific genetic polymorphisms of Cps and Che have yielded little information, limiting the ability to understand the evolution and migration of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…All additional available genome sequences for Calonectria spp. published to date ( Malapi-Wight et al 2016a , b , 2019 , Ye et al 2017 , LeBlanc et al 2019 ) were also screened for inclusion in this study of the mating type locus. These included three genome sequences of Ca.…”
Section: Methodsmentioning
confidence: 99%
“…All additional available genome sequences for Calonectria spp. published to date ( Malapi-Wight et al 2016a , b , 2019 , Ye et al 2017 , LeBlanc et al 2019 ) were also screened for inclusion in this study of the mating type locus. These included three genome sequences of Ca.…”
Section: Methodsmentioning
confidence: 99%
“…However, in 2005, a second species— Che was identified from diseased boxwood in the UK and continental Europe [ 24 ]. Several studies have shown limited genetic diversity from natural populations of Che and Cps , consistent with the hypothesis of predominant asexual reproduction and introduced clonal lineages [ 8 , 37 , 38 ]. Malapi-Wight et al (2019) determined that populations of Cps have a single mating type idiomorph (MAT1-1) compared to populations of Che which possess the MAT1-2 idiomorph [ 44 ].…”
Section: Introductionmentioning
confidence: 62%
“…Malapi-Wight et al (2019) determined that populations of Cps have a single mating type idiomorph (MAT1-1) compared to populations of Che which possess the MAT1-2 idiomorph [ 44 ]. Separate studies demonstrated that pathogen populations have low genetic diversity and no evidence of sexual recombination, suggesting limited opportunities for mating with predominately clonal asexual reproduction [ 8 , 37 ]. Despite possessing opposite mating types and a sympatric geographic distribution in Europe and the UK, successful mating between Che and Cps has not been observed in nature or under laboratory conditions [ 7 , 37 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the widespread global distribution of Cps, Che is presently detected only in six European countries: Belgium, the Czech Republic, Germany, the Netherlands, Slovenia, and the United Kingdom (Bartíková et al 2020a(Bartíková et al , 2020bLeBlanc et al 2019) (Fig. 7).…”
Section: Geographic Distributionmentioning
confidence: 92%
“…Because the LAMP assays are based on isothermal DNA amplification, they do not require the use of thermal cyclers. Whole-genome sequences have also been used to confirm the identity of Cps isolates (Malapi-Wight et al 2016b), and several genome sequences are publicly available for both Che and Cps for comparative use (Crouch et al 2017;LeBlanc et al 2019).…”
Section: Molecular Methods For Pathogen Detectionmentioning
confidence: 99%